Measuring The Level of Employee Performance and The Factors that Influenced at PT Gici Group Batam - Setiawan, Joko; Panjaitan, David (Program Studi S3 Ilmu Manajemen, 2023)
This research is to determine and analyze the factors Compensation, Loyalty and Organizational Commitment influence on Employee Performance at PT Gici Group Batam. Results Data collection obtained sample of 87 respondents. Respondents in this study were employees of PT Gici Group Batam. The analytical method used is multiple regression analysis, using Pearson rank validity test and Cronbach-Alpa reliability test against research instruments. To assess the influence of compensation, loyalty, and organizational commitment influence on employee performance in PT Gici Group Batam, used path analysis. After doing research and testing show Compensation, Loyalty, and Commitment of organization have positive and significant effect on employee performance.